Comparison between intraoperative bleeding score and ROTEM® measurements to assess coagulopathy during major pediatric surgery. (October 2021) - Restin, Tanja; Schmugge, Markus; Cushing, Melissa M.; Haas, Thorsten
Abstract: Purpose: Intraoperative bleeding should be regularly assessed visually to guide coagulation management. Whereas viscoelastic testing with ROTEM® measurement has been proven to be useful in detecting coagulopathies, the visual assessment is not standardized. This study therefore aims to compare a standardized visual assessment with ROTEM® results. Methods: A 5-point bleeding score was created and applied in a recently published randomized controlled trial in major pediatric non-cardiac surgery. This score assesses overall bleeding tendency and the occurrence of diffuse bleeding, aqueous bleeding, bleeding outside the operative field, and the ability to control bleeding. Validity of this score was tested by post hoc comparison to the results of simultaneously performed ROTEM® measurements. Results: Signs of coagulopathic bleeding were assessed at 183 time points. Mild to moderate bleeding intensity was judged at 103 time points, in 42 % abnormal ROTEM® traces were obtained simultaneously. When severe bleeding was scored, abnormal ROTEM values occurred in 58 %, and FIBTEM-values were significantly lower than in the "no bleeding group". Altogether, the correlation between bleeding score and ROTEM® measurements was not significant. Conclusions: The standardized visual assessment did not correlate well with ROTEM® measurements, suggesting that it is not useful to detect coagulopathy. Trial registry number: ClinicalTrials.gov identifier No. NCT01487837.